Profit intensity criterion for transportation problems - M. Voynarenko; A. Kholodenko (Global Journal of Environmental Science and Management)
In this study criterion of maximum profit intensity for transportation problems, in contrast to the known criteria of minimum expenses or minimum time for transportation, is considered. This criterion synthesizes financial and time factors and has real economic sense. According to the purpose of this paper, the algorithm of the solution of such a transportation problem is constructed. It is shown that the choice is carried out among Pareto-optimal options. Moreover, the factor of time becomes defining for the high income from transportation, and the factor of expenses – at low ones. Not absolute but relative changes of numerator and denominator become important when the criterion represents the fraction (in this case – the profit intensity as the ratio of profit to time). A nonlinear generalization of such transportation problem is proposed and the scheme of its solution in a nonlinear case is outlined. Graphic illustrations of Pareto-optimal and optimal solutions of transportation problem by profit intensity criterion are also given.